Interactions of Residents Who Have Intellectual Disability and Challenging Behaviours. Issue 1 (2nd January 2020) - Nankervis, Karen; Ashman, Adrian; Weekes, Alysia; Carroll, Michael
ABSTRACT: A high proportion of adults with intellectual disability (ID) who live in supported accommodation (i.e. group homes) engage in challenging behaviours (CB). A lack of engagement in meaningful activity, social isolation, communication difficulties, and boredom can be triggers for challenging behaviour. There is a small body of literature on staff/resident interactions in the context of challenging behaviour but even less research has addressed resident-to-resident interactions. Specific Aims : This study aims to examine the types of interactions in which residents of shared accommodation settings engage, with whom; and explore staff's understanding of residents' needs, communication abilities, and relationships. Method Observations of interactions with 12 residents who were identified as having challenging behaviours were conducted using momentary time sampling. Direct care staff who supported the residents were also interviewed. Findings : Residents were infrequently engaged in activity or interactions and where these did occur, they were primarily with staff rather than with co-residents. Discussion : Staff play an important role in supporting and facilitating people with ID and CB to expand their social interactions and engagement in meaningful activity, which can have a significant impact on the occurrences of challenging behaviour. The implications for practice in shared accommodation sites are discussed.